Analisis Kelayakan Usaha Tahu Kriuk Sebagai Salah Satu Inovasi UMKM Guna Meningkatkan Selera Masyarakat - Lusi Lusmawati; Della Filiyanti; Siti Noer Hafifah; Intan Roisah Maulidah; Nuril Aprisia Rokhmawan; Taufiqurrozzaq Taufiqurrozzaq (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Rational thinkers need the ability to think critically but it is not enough just to do that, it must be with real and visible evidence. In this discussion the author uses a quantitative method with a descriptive approach which makes it possible to answer questions that require absolute answers, namely by presenting the evidence that exists because absolute truth cannot be seen through mystical/prological thinking.